Transmission dynamics of sunflower mosaic virus: insights into mechanical and aphid-mediated spread: DYNAMICS OF SUNFLOWER MOSAIC VIRUS: MECHANICAL AND APHID-MEDIATED SPREAD - SANGEETA SABANNA BHAJANTRI; B N ASHWINI; SWATHI; SIDDU LAKSHMI PRASANNA (Journal of Oilseeds Research, 2026)
Sunflower mosaic virus (SuMV) is an economically important pathogen of sunflower, disseminated primarily through mechanical inoculation and aphid vectors. Mechanical transmission produced characteristic symptoms including mosaic, mottling, leaf puckering, chlorotic rings, lamina reduction and stunting with disease incidence reaching up to 42%. The highest mechanical transmission was achieved using phosphate buffer (pH 7.0) supplemented with 0.5% sodium sulphite. Aphid (Aphis gossypii) transmitted SuMV in a non-persistent manner with 16-24% efficiency. Transmission efficiency was maximized when aphids underwent a 60 min pre-acquisition starvation period, followed by 15 min acquisition feeding and 15 min inoculation feeding. These findings provide valuable insights into the epidemiology of SuMV and contribute to formulating effective management strategies against sunflower viral diseases.